Negocjacje w integrującej się Europie - aspekt kulturowy - Kałążna-Drewińska, Urszula (Negotiations in the Integrating Europe - the Cultural Aspects, 2008)
The paper addresses the issues of: cultural conditioning of negotiation behaviour, impact of culture on negotiation, models of cultural behaviour, similarities and differences in cross-cultural negotiation behaviours of various EU nations.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 17, s. 55-62